Practicing creative thinking skills: Inquiry base activity sheets development in protists learning material - Rossanita Truelovin Hadi Putri; Raharjo Raharjo; Fida Racmadiarti (JPBIO (Jurnal Pendidikan Biologi), 2021)
Protist learning materials have been developed by many researchers, but no one has developed learning tools by training students' creative thinking skills. This study aims to produce LKPD based inquiry on protist material and to train creative thinking skills, by describing the validity and effectiveness of LKPD on protist material. The LKPD developed refers to the 4D model which consists of the stages of define, design, develop, and disseminate. The research design used was the One-Group Pretest-Posttest Design. LKPD was tried out on 12 students of class XI MIPA SMA. After using LKPD, the validity and effectiveness data were analyzed descriptively quantitatively. The validity of the LKPD is measured based on the assessment of the education expert lecturers and materials. The effectiveness of protist LKPD is measured based on the learning outcomes of students and students' responses. The results showed the validity of the LKPD was 99.4% with the very valid category. The effectiveness based on the learning outcomes of students was 92% with the category very effective and the response of students was 99%. Based on the results of this assessment, it can be concluded that LKPD based on the inquiry on protist material to train creative thinking skills is declared valid and effective.Keywords: Activity sheets, inquiry learning, creative thinking, protists